Bactericidal effect of hyperbaric oxygen therapy in burn injuries. (February 2022) - Oley, Mendy Hatibie; Oley, Maximillian Christian; Wewengkang, Louise A.J. Waworuntu; Kepel, Billy Johnson; Langi, Fima Lanra Fredrik G.; Setiadi, Taat; Aling, Deanette Michelle R.; Gunawan, Deborah Florencia; Tulong, Marcella Tirsa; Faruk, Muhammad
Abstract: Introduction: Burn injuries are frequently encountered in emergency cases and often become the port of entry for pathogens. More than 450, 000 burn injuries occur annually causing nearly 3, 400 deaths in the United States. The prevalence of burn injury in Indonesia is 0.7% in 2013. More than half of these According to several studies on the use of patients were treated for bacterial infections, some of which were resistant to certain antibiotics. Using hyperbaric oxygen therapy (HBOT) to treat burns has several positive effects including managing bacterial infections, as well as accelerating the wound healing process. Therefore, this study aims to prove the effectiveness of HBOT in inhibiting bacterial growth. Methods: This is an experimental research study in rabbits using a post-test control group design. 38 rabbits were given second-degree burns on the shoulder region with a metal iron plate that has been previously heated for 3 min. Bacterial cultures were taken on days 5 and 10 after exposure to the burns. The samples were divided into two groups, HBOT and control. Statistical analyses were performed using the Mann-Whitney U method. Results: Gram-negative bacteria were the most frequently found pathogen in both groups . Citrobacter freundi was the most common Gram-negative bacteria (34%) found in the culture results of both groups. In contrast to the control group, there was no bacterial growth found in the HBOT group's culture results, (0%) vs (58%). A significant reduction of bacterial growth was observed in the HBOT group (69%) compared with the control group (5%). Bacterial levels stagnated in 6 rabbits (31%) in the HBOT group and 7 rabbits (37%) in the control group. Overall, there was significantly less bacterial growth in the HBOT treatment group compared with the control group (p < 0.001). Conclusion: HBOT administration can significantly reduce bacterial growth in burn injuries. Highlights: Hyperbaric oxygen therapy (HBOT) to treat burns has several positive effects including managing bacterial infections. HBOT influence the extent of a bacterial infection based on reduced bacterial counts after receiving HBOT. The bactericidal effects of HBOT are obtained by inducing the release of reactive oxygen species.